Dopamine in nucleus accumbens: salience modulation in latent inhibition and overshadowing - Nelson, Andrew J.D.; Thur, Karen E.; Marsden, C.A.; Cassaday, Helen J. (Sage, 2012)
Latent inhibition (LI) is demonstrated when non-reinforced pre-exposure to a to-be-conditioned stimulus retards later learning. Learning is similarly retarded in overshadowing, in this case using the relative intensity of competing cues to manipulate associability. Electrolytic/excitotoxic lesions to shell accumbens (NAc) and systemic amphetamine both reliably abolish LI. Here a conditioned emotional response procedure was used to demonstrate LI and overshadowing and to examine the role of dopamine (DA) within NAc. Experiment 1 showed that LI but not overshadowing was abolished by systemic amphetamine (1.0 mg/kg i.p.). In Experiment 2, 6-hydroxydopamine (6-OHDA) was used to lesion DA terminals within NAc: both shell- and core- (plus shell-)lesioned rats showed normal LI and overshadowing. Experiment 3 compared the effects of amphetamine microinjected at shell and core coordinates prior to conditioning: LI, but not overshadowing, was abolished by 10.0 but not 5.0 µg/side amphetamine injected in core but not shell NAc. These results suggest that the abolition of LI produced by NAc shell lesions is not readily reproduced by regionally restricted DA depletion within NAc; core rather than shell NAc mediates amphetamine-induced abolition of LI; overshadowing is modulated by different neural substrates.